2023
DOI: 10.3390/ani13030494
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Replacement by Alternative Protein Sources in Pig Nutrition and Its Effect on Meat Quality

Abstract: Soybean is one of the most expensive and limiting feed ingredients in diet formulations; however, in pig farming, it represents the main source of protein. The production and supply of soybean are critical steps due to their environmental impact and feed/food competition for land use. Therefore, research is focusing on finding alternatives to replace soybean partially or totally. However, alternative ingredients should ensure similar growth performance, carcass traits, and meat quality characteristics compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 92 publications
2
10
0
Order By: Relevance
“…Similarly, Fiszeder and Orzeszko [54] attributed the lack of causal effects between livestock market and soybean price to the fact that cattle are not a huge consumer of soybeans, and therefore such a result is expected. The low usage of soybeans in livestock feeds is attributed to soybean's status as one of the most expensive protein sources in feed rations [55]. Secondly, South Africa's soybean production has experienced significant growth in recent years, accompanied by a substantial increase in soybean processing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fiszeder and Orzeszko [54] attributed the lack of causal effects between livestock market and soybean price to the fact that cattle are not a huge consumer of soybeans, and therefore such a result is expected. The low usage of soybeans in livestock feeds is attributed to soybean's status as one of the most expensive protein sources in feed rations [55]. Secondly, South Africa's soybean production has experienced significant growth in recent years, accompanied by a substantial increase in soybean processing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies found no difference when comparing diets with substitution with diets without substitution [ 126 , 127 , 128 ]. On the other hand, other studies found that diets with substitution caused poultry [ 129 ] and pigs [ 130 ] to gain less weight. The findings of various investigations were compiled by Guo et al [ 131 ], who found that pigs with a substitution rate of 50% had a growth rate that was 13% slower.…”
Section: Meat Quality and Animal Growthmentioning
confidence: 99%
“…The production and supply of soybean are critical due to their environmental impact and feed competition for land use [4,5]. There have been many attempts to find alternative feed ingredients as protein sources in pig diets [6]. Most of the ingredients recently studied are vegetable resources, especially local species well-adapted to specific climatic conditions, such as lupin seed, canola cake, guar, sainfoin, taro, and…”
Section: Introductionmentioning
confidence: 99%